The heterogeneity among subgroups of haplogroup J influencing Alzheimer’s disease risk - Liu, HaoChen; Zhang, Yixuan; Zhao, Huimin; Du, Yanan; Liu, XiaoQuan (Journal of advanced research, 2021)
[Display omitted] •There is heterogeneity among subgroups of haplogroup J which influences AD risk.•The heterogeneity among haplogroup J influences the MCI-to-AD conversion risk.•The heterogeneity among subgroups of haplogroup J is independent of Aβ and p-tau. The impact of mitochondrial haplogroups on Alzheimer’s disease (AD) risk has not been fully elucidated and warrants further investigation at the subgroup level. The aim of this research is to evaluate the association between mitochondrial haplogroups and AD risk in subgroups level. In total, 809 AD Neuroimaging Initiative subjects were assessed using mtDNA sequencing, the AD Assessment Scale-Cognitive Subscale (ADAS-cog), hippocampal volume measurements, the hypometabolic convergence index (HCI), and MCI-to-AD conversion proportion measurements. The frequency of haplogroup J was significantly higher than that of other haplogroups in the AD group (p = 0.013). According to the correlation between haplogroup J-specific SNPs and ADAS-cog, haplogroup J was divided into four subgroups harboring exacerbating SNPs, protective SNPs, both exacerbating and protective SNPs, or irrelevant SNPs. The subgroups harboring exacerbating SNPs exhibited higher AD risk represented by the levels of ADAS-cog, hippocampal volume, HCI, and MCI-to-AD conversion proportion than other subgroups. Heterogeneity existed among the subgroups of haplogroup J, which suggested that different subgroups exhibited different levels of AD risk. This study provides novel insights into the correlation between mitochondrial haplogroups and AD risk.